2022
DOI: 10.3389/fcell.2022.817877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lysosomal Acidification Dysfunction in Mesenchymal Stem Cell Senescence

Abstract: Mesenchymal stem cell (MSC) transplantation has been widely used as a potential treatment for a variety of diseases. However, the contradiction between the low survival rate of transplanted cells and the beneficial therapeutic effects has affected its clinical use. Lysosomes as organelles at the center of cellular recycling and metabolic signaling, play essential roles in MSC homeostasis. In the first part of this review, we summarize the role of lysosomal acidification dysfunction in MSC senescence. In the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 112 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Besides the induction of cell death pathways, disruption of the lysosomal pH and loss of lysosomal integrity have consequences on various cellular processes. The neutralization of lysosomal pH impairs the degrading activity of lysosomes essential for recycling and scavenging, and can cause the formation of toxic digestion products or reactive oxygen species (ROS) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the induction of cell death pathways, disruption of the lysosomal pH and loss of lysosomal integrity have consequences on various cellular processes. The neutralization of lysosomal pH impairs the degrading activity of lysosomes essential for recycling and scavenging, and can cause the formation of toxic digestion products or reactive oxygen species (ROS) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lysosomes contain a variety of degrading enzymes. 2–5,50 These enzymes, such as Cathepsin B enzyme exert the highest biological activity in an acidic environment (pH 4.5–5.0), and lysosomal alkalization leads to a decrease or deactivation in the activity of lysosomal hydrolytic enzymes. 14,38 Thus, we tested the effect of compounds 1–12 on the activity of Cathepsin B enzyme using a Magic Red Cathepsin assay.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that lysosomes are membrane-bound subcellular organelles and maintain cellular homeostasis by generating a highly acidic environment. 1 Lysosomal enzymes are responsible for breaking down carbohydrates, nucleic acids, lipids and proteins, 2–6 and usually exert the maximal activity in an acidic environment (pH 4.5–5.0). 7–14 Leakage of protons due to a defective proton pump or lysosomal permeabilization would lead to lysosomal alkalization and consequently a decrease or deactivation in the activity of lysosomal hydrolytic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…ALP impairment is widely observed in AD and other neurodegenerative diseases [ 3 , 70 ]. Some studies have suggested that lysosome alkalinization may cause rupture of lysosomes and lead to premature release of undigested content [ 71 ]. Therefore, it is believed that alkaline lysosomes are more harmful than acidic lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our data suggest that hyperphosphorylated tau leads to TPC2 overactivity and impairs ALP function in neurons via lysosome alkalinization. Impairment of ALP-mediated clearance of tau may lead to premature release of undigested content and promote tau seeding and transmission [ 66 , 71 ]. Microglia can cease such transmission by scavenging these aggregates [ 35 , 78 ].…”
Section: Discussionmentioning
confidence: 99%